Decision Support System Development Based On Android Using Analytical Hierarchy Process (AHP) Method For Determining The Middle Small Business Development Priority In Sorong City - Luluk Suryani; Raditya Faisal Waliulu; Ery Murniyasih (Electro Luceat, 2019)
Usaha Kecil Menengah (UKM) is one of the economic drivers of a region, including the City of Sorong. UKM in Sorong City have not yet developed optimally. There are several causes including those concerning financial, location, raw materials and others. To solve these problems, researchers are encouraged to develop applications that can help determine the priorities of UKM in accordance with the conditions of business people. In this study, the Analytical Hierarchy Process (AHP) method will be used for decision making. AHP method was chosen because it is able to select and determine the best alternative from a number of available alternatives. In this case the intended alternative is the best UKM that can be chosen by businesses in accordance with predetermined criteria. The study was conducted by finding the weight value for each attribute, then ranking process will determine the optimal alternative, namely UKM. Decision Support System application developed based on Android, where users will easily use it at any time if there is a change in weights on the criteria or intensity. The final results show that the AHP method was successfully applied to the UKM Development Priority Determination Application.